How Does Militant Violence Diffuse in Regions? Regional Conflict Systems in International Relations and Peace and Conflict Studies - Ansorg, Nadine (International Journal of Conflict and Violence (IJCV), 2011)
Regional conflict systems are characterised by their complexity of actors, causes, structural conditions and dynamics. Such complexity poses difficulties to those looking to undertake scientific analysis of the regional dynamics of violence. It is still quite unclear how militant violence diffuses in regions and under which conditions a regional conflict system can emerge. This review of existing approaches to regional conflict dynamics in international studies and peace and conflict studies focuses on how the regional conflict dynamics and the causal mechanisms behind the development of regional conflict systems are dealt with, considering process dynamics in space and time as well as in the interactions between possible causal factors. The primary gaps in existing research are identified and possible new research directions sketched out.Regional conflict systems are characterised by their complexity of actors, causes, structural conditions and dynamics. Such complexity, however, poses difficulties to those looking to undertake scientific analysis of these processes. In the present paper existing approaches to regional conflict dynamics in international studies and peace and conflict studies are reviewed. Of particular interest is the question how these approaches dealt with regional violence in areas with limited or no statehood as this is one of the striking conditions for the emergence and diffusion of regional conflict systems. Starting from this question, the main research gaps that exist in the current literature on regional conflicts will be detected. Furthermore, new research directions will be pointed out.